Experiential learning of ethnopharmacological sources of drugs through rotating trios micro discussion in MBBS students: an innovative I-tray teaching methodology - Imran, Mohammed; Doshi, Chintan M.; Kharadi, Darshan; Naaz, Saima (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Complementary and alternative medicine is very robust in some parts of the world. The study was done to impart the experiential learning related to sources of drugs in a pharmacy practical class for MBBS students. Methods: We used ingredient-tray (I-Tray) teaching tool consisting of two parts to generate experiential learning in MBBS students about ethno pharmacological sources of drugs. Innovatively designed I -tray filled with two sizes plastic containers (100 ml and 50 ml sizes used for collecting biological samples of sputum and urine) containing crude drug medicinal sources which were arranged in gutters of the tray. They were sorted into five categories such as plants (flowers of Vinca rosea, bark of Terminalia arjuna, roots of Rauwolfia serpentine and Eucalyptus leaves); animals (formalin preservatives freshwater leech, shells and vaccines); minerals (kaolin, potassium permanganate and charcoal); oils and others. Three charts of 4 square feet sizes were used for demonstration of synthetic, microbiological and genetically engineered drug sources. Results: The students’ approval rate of I-tray was mean yes value of 105.78 for a tool of active learning out of total 113 students. Around 100%, 98.23 % and 97.35% students utilised application of concept (cognition), faculty of smell (affective) and volunteering (psychomotor) in the class. However female students had statistically significant score against this set up of the class depicting gender specificity of the learning process. Conclusions: Thus teaching traditional sources of drugs through I-tray impart higher order social, place based and experiential learning of medicine.